2021
DOI: 10.1111/hiv.13148
|View full text |Cite
|
Sign up to set email alerts
|

Immune reconstitution inflammatory syndrome‐associated Graves disease in HIV‐infected patients: clinical characteristics and response to radioactive iodine therapy

Abstract: Objectives We aimed to describe the clinical characteristics and the response to radioactive iodine (RAI) treatment of immune reconstitution inflammatory syndrome‐associated Graves disease (IRIS‐GD) in comparison to Graves disease (GD) seen in HIV‐uninfected patients. Methods We retrospectively reviewed the medical records of patients treated with RAI for GD. We obtained clinical, biochemical and HIV‐related information of patients from their medical records. We compared patient characteristics and response to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 26 publications
(35 reference statements)
0
8
0
Order By: Relevance
“…The institution of ART in these severely immunosuppressed patients often leads to the apparent worsening of existing opportunistic conditions and the appearance of new inflammatory/infectious conditions due to an exaggerated immune response to foreign and self-antigens, the so-called immune reconstitution and inflammatory syndrome (IRIS). 81,82 The institution of ART in patients on ATT for TB may lead to the paradoxical worsening of disease symptoms and image findings. 83 FDG PET/CT obtained in these patients for interim response assessment during the process of IRIS may show worsening of disease (increased FDG avidity in lesions, new pulmonary and extrapulmonary lesions).…”
Section: Fdg Pet/ct For Tb Treatment Response Assessmentmentioning
confidence: 99%
“…The institution of ART in these severely immunosuppressed patients often leads to the apparent worsening of existing opportunistic conditions and the appearance of new inflammatory/infectious conditions due to an exaggerated immune response to foreign and self-antigens, the so-called immune reconstitution and inflammatory syndrome (IRIS). 81,82 The institution of ART in patients on ATT for TB may lead to the paradoxical worsening of disease symptoms and image findings. 83 FDG PET/CT obtained in these patients for interim response assessment during the process of IRIS may show worsening of disease (increased FDG avidity in lesions, new pulmonary and extrapulmonary lesions).…”
Section: Fdg Pet/ct For Tb Treatment Response Assessmentmentioning
confidence: 99%
“…Although the pathogenic mechanism of GD-IRIS is not completely known, it seems to be a consequence of an immunoregulatory disequilibrium, characterized by thymic enlargement, failure of thymic deletion of autoreactive T-cells, persistence of T-cell receptor excision circle levels in CD4 and lymphocytes T CD8+ (CD8), and high circulating levels of naïve CD8 [ 59 , 65 ]. It seems that immune reconstitution promotes a profile shift in cytokines production from TH2 to TH1 types, permissive for the development of autoimmunity events [ 66 ].…”
Section: Autoimmune Thyroid Diseasesmentioning
confidence: 99%
“…Radioactive iodine (RAI) treatment is an increasing therapy used either as first-line treatment or as an alternative treatment in patients who do not tolerate or respond to medical therapy. RAI treatment is based on the principle that the thyroid gland entraps iodine and uses it for THs production; thus, once inside the thyroid follicular cells, RAI releases energetic beta particles, leading to the destruction of the follicular cells [ 65 ]. A recent retrospective study showed that there is no difference in response to RAI treatment between PLWH with IRIS-GD and GD in HIV-uninfected patients [ 65 ].…”
Section: Autoimmune Thyroid Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the era of HAART (highly active retroviral therapy), the autoimmune diseases of HIV infected patients after treatment mainly occur at the phase of immunological recovery [ 1 ]. The inflammatory syndrome related Graves' disease, occurs after HIV infected patients begin immune reestablishment on antiretroviral therapy at an advanced stage of the disease [ 2 ]. The reason may be that the expansion of naive T cells and primary transplanted CD4T cells and the increase of autoantibody titers lead to the development of organ-specific autoimmune diseases [ 3 ].…”
Section: Introductionmentioning
confidence: 99%